Soft tissue reconstruction for craniofacial surgery planning - Rana, Mohammad Azam (2006)
Computer Assisted Surgery (CAS) systems strive to enhance the surgeon’s capabilities to utilize medical imagery to decrease the invasiveness of surgical procedures and increase their accuracy and safety. Image guided surgery systems facilitate surgical planning and analysis by aligning various datasets with information on morphology (MR, CT, MR angiographies), cortical function (fMRI) or metabolic activity (PET, SPECT). These systems are categorized into performing one or more of the functions such as data analysis, surgical planning and surgical guidance, etc. The surgical planning systems present surgeons with data gathered prior to surgery and facilitate in plotting an approach trajectory that avoids critical structures such as blood vessels etc. Computer tomography (CT) and magnetic resonance imagery (MRI) has had an enormous impact in medicine during the past two decades and has been widely used for surgical planners. Craniofacial anomalies and fine anatomic details of facial traumic injuries can be well studied with such imaging techniques. The research focuses on development of a system for simulation of craniofacial reconstruction surgery that is based on volumetric object models derived from 3D Computer Tomography (CT) imaging. Feedback is provided to the user via real-time volume rendering. The system is the result of collaboration between a university, an industrial research organization and a research hospital. In this paper, components of the system are detailed and the current state of the integrated system is presented. Issues related to future research and plans for expanding the current system are discussed.